Wounds to Words: Trauma and Transformation in Salman Rushdie’s Knife - Pokharel, Bishnu Prasad; Banu, Sultana; Sapkota, Binod (Nepal Journal of Multidisciplinary Research, 2025)
Background: Salman Rushdie’s memoir Knife: Meditations After an Attempted Murder explores how writing serves as a therapeutic tool for the author following a physical attack by "A" in New York while he was preparing to provide a public speech. Methodology: This study employs a qualitative analysis of the memoir, primarily drawing on Cathy Caruth’s trauma theory, with supporting details from other theorists. Applying the theory, this study reconnoiters the function of writing to heal the person who has bodily and mental illness. Findings: The textual analysis that applies trauma theory suggests that reading and writing can help erase corporeal and psychological trauma for individuals. The narrator, who is also the speaker, reconciles mental trauma by using memoir writing as a therapeutic tool. This is why writing serves to maximize joy and happiness while minimizing suffering. Conclusion: Thus, this study deduces that writing functions as a source of solace for traumatic mindset. The longing for life intensifies as the writer begins to write and elaborate on the shared imaginary conversation with the attacker. Novelty: Narrative and conversational words are the key elements that help people feel psychologically refreshed, allowing them to forget the terror of physical assaults or emotional underestimations. The imaginative dialogue erases the speaker's hatred towards the attacker, which in turn mentally heals him. Therefore, memoir writing is a form of therapy that energizes materially and heals spiritually.